NaNO3 sensing based on microfiber coated with multi-walled carbon nanotubes - Yasin, Moh; Irawati, Ninik; Harun, Sulaiman Wadi; Khasanah, Miratul; Ahmad, Fauzan (Elsevier, 2019)
Sodium nitrate (NaNO 3 ) refractive index sensor was proposed and demonstrated by using a microfiber structure, which was coated with multi-walled carbon nanotubes (MWCNTs). In the proposed sensor, we used a flame brushing technique to fabricate microfiber and drop coating method for coating of MWCNTs thin layer. It is observed that the change of the spectrum's output power and peak wavelength are more obvious with the coating. The presence of MWCNTs on the surface microfiber works as passive cladding and influence the light propagation through the fiber. The sensitivity and resolution of the sensor has reached 1.015 dB/% and 0.008%, respectively. © 2019 Elsevier GmbH